PROGRAM EKONOMI KERAKYATAN BIDANG PERIKANAN KABUPATEN KAMPAR TAHUN 2011-2013 - Saputra, Engla Boy Doli; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Implementation of program ekonomi kerakyatan in fisheries Kabupaten Kampar 2011-2013, the providence of rolling fund in Desa Koto Mesjid encounter some problem, one of them is the process of fund return of the rolling fund that is not coherse with the villagers expectation. The goal of the spirit of implementation of program ekonomi kerakyatan that point to Tri Sukses that is, success in the distribution, success in the achievement, and success in the return. This is the reason that i become interested to study in my research. The main problem in my research is “why the implementation of program ekonomi kerakyatan in fisheries, providence of the rolling fund in Desa Koto Mesjid Kecamatan XIII Koto Kampar still not implemented effectively.The goal of this research is to understand the process mechanism of the implementation of the program ekonomi kerakyatan in fisheries Kabupaten Kampar 2011-2013, providence of rolling fund in Desa Koto Mesjid, and than to analize the implementation of program ekonomi kerakyatan in fisheries, and than study about the obstacle in the implementation. This research is done in Desa Koto Mesjid Kecamatan XIII Koto Kampar Kabupaten Kampar. This research is using quantitative research metode with descriptive metode in collecting data. Researcher using the method of interview, observation, and dokumentation with a key informan as the main resource of information and using multiple question to the informan with observing the fenomenon that exist in the legality of the datas.Based in the research that is concluded that the process of the implementation and the obstacle in program ekonomi kerakyatan in fisheries Kabupaten kampar 2011-2013, providence of the rolling fund is not implemented efectively and not coherse with the guide provided in Peraturan Bupati Nomor 7 Tahun 2013 about the guide of the implementation of the rolling fund program ekonomi kerakyatan kabupaten kampar.Keywords : Program Ekonomi Kerakyatan, Providence of the rolling fund, Fisheries Agency Kabupaten Kampar.